The Effects of Implementing Vocabulary Journals into Main Course Classes on Student Success at a Private University - Turnuk, Tulin (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
Vocabulary learning is one of the most difficult components of foreign language education. Therefore, students are in need of some strategies to cope with it and keeping vocabulary journals is one of these particular strategies. This study examined the vocabulary journals kept by the preparatory school students of a private university to determine the effects of them on learner success and learner autonomy as well as the attitudes of students and instructors towards them. A mixed method approach in which qualitative data was supported by quantitative data was applied to totally 346 participants. The findings of the study provide relevant information and insight for the instructors and administrators who aim to enhance vocabulary learning and plan to implement vocabulary journals into their own educational systems. Keywords: vocabulary journal, vocabulary learning, retention, learner autonomy, homework